Analytical investigation of step-square wave in time and frequency domain using transform equations - Fajingbesi, Fawwaz Eniola; Midi, Nur Shahida; Khan, Sheroz (Institute of Physics Publishing, 2017)
A unit step function can be used for generating a pulse of given width and height. The same pulse can be used for generating a stepped waveform of known levels and a given width in time-domain which when translated to frequency or complex S-domain provides the fundamental constituent frequencies. This paper is about studying the frequency of the above-generated functions in time as well in the frequency domain using transform equations. The result of this simulations are indicative of the correlation between step square waving and reductions in total harmonic distortion (THD) during DC to AC conversion. A decrease in the pulse width difference between each step shows better conversion with reduced harmonics when subjected to simple passive filter of low transfer function.